Design Of Decision Support Systems Determining Priority Customers PT. XYZ with Topsis Method Web Based - Mayrizkiy, Muhamad Dafhi; Mulyati, Mulyati (Politeknik Negeri Lhokseumawe, 2025)
The priority customer assessment process at Company XYZ has a direct influence on increasing the company's operational profits. There are problems in determining priority customers by companies resulting in reduced efficiency and the potential for financial losses due to the use of random, manual and individual opinion-based selection methods, causing significant waste of time. The aim of this research is to design a Decision Support System (DSS) based on the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) which can help the priority customer assessment process effectively. This system has several assessment indicators that are used to assess priority customers, namely number of orders, length of subscription, amount/nominal payment, payment history. The results of testing and system implementation show that Customer D's alternative received the highest score, namely 0.839, followed by other alternatives with appropriate assessments. With the TOPSIS method, company XYZ can make better decisions related to the weight of the criteria based on the provisions of the criteria that have been determined and can determine the weight of the criteria objectively, prioritize criteria based on customer eligibility levels, and speed up the assessment process. As a result, assessments become fairer, more accurate and in line with company expectations.